Five Percent Post Survey Check Of National Family Health Survey (NFHS) In ORISSA - Kumar Benera Sudhir; Singh Padam (Wolters Kluwer Medknow Publications, 1999)
Research questions: How well a post survey sample check of NFHS correlates with the findings of NFHS? Objective: Post survey check of National Family Health Survey carried out in 1992-93. Study design: Multistage sampling method with 5 percent sample of original NFHS sample. Setting: Study covered 5 percent sample of original NFHS sample. Subjects: Five percent household sample (1093 members) of original NFHS sample was studied and compared with NFHS data. Method: Information from five percent house-holds of NFHS in which either there likely to be no change was likely to be only in one direction such as age group, sex-ratio, literacy, family planning knowledge and adoption etc. were collected in a predesigned questionnaire and compared with NFHS data. Results: The demographic characteristics were similar to those of NFHS. TFR and number of children ever borne were also found to be same. The awareness of FP methods and its uses were within acceptable margin of error. Thus on comparison of data of post survey check and NFHS sample error was within acceptable margin.